It is not clear if the denominator of the ratio is just x or is (x+tan x).

This thing must be specified with the help of the brackets.

If the denominator of the ratio is x:

lim [sin(x)/x+tan(x)] = lim [sin(x)/x] + lim tan(x)

lim [sin(x)/x] is an elementary limit and the result is1.

We'll calculate lim tan x.

We'll substitute x by the value 0.

lim tan x = tan 0 = 0

So, the limit is:

**lim [sin(x)/x+tan(x)] = 1 + 0 = 1**

Now, if the denominator is (x+tan x), we'll calculate the limit:

lim [sin(x)/(x+tanx)] = sin 0/(x + tan 0)

lim [sin(x)/(x+tanx)] = 0/0

"0/0" is an indetermination

We'll use l'hospital rule. We'll differentiate separately numerator and denominator.

(sinx)' = cos x

(x+tanx)' = 1 + 1/(cos x)^2

lim [sin(x)/(x+tanx)] = lim (sinx)'/(x+tanx)'

lim (sinx)'/(x+tanx)' = lim cos x/[1 + 1/(cos x)^2]

We'll substitute x by 0:

lim cos x/[1 + 1/(cos x)^2] =cos 0/[1 + 1/(cos 0)^2]

cos 0/[1 + 1/(cos 0)^2] = 1/(1+1) = 1/2

**lim [sin(x)/(x+tanx)] = 1/2**

The limit of sinx/x+tanx, as x-->0.

Solution:

The most difficult symbol of slash "/"

Do you mean (i) sinx/x+tanx = [(sinx)/x ]+tanx or (ii) (sinx)/(x+tanx)?

We answer both cases.

(i)

The limit of sinx/x + tanx = lt sinx/x +lt tanx = 1+0 =1.

The second term lttanx is got by just by substitution of x=0 in tanx which gives tan0 = 0.

The lt of sinx/x is of special interest , as putting 0 in (sinx)/x becomes sin0/0 which is a 0/0 form of indetermination.

So we can use L'Hospital's rule of diffrentiating the numerator and denominator and then take the limit. Or we can go for the geometrical proof where (sinx/x) remains between cosx and 1 as x approaches zero. But cosx approaches 1. So Limit (sinx)/x should also approach 1.

Lt of (sinx)/x by L'Hospital's rule :

Lt x--> 0 (sinx)/x = Lt x-->0 (sinx)'/ (x)' = Lt x-->0 (cosx)/1 = cos0 = 1.

So lt (sinx)/x = 1.

Therefore Lt {(sinx)/x +tanx} = 1+0 = 1.

(ii) To find the lt x--> 0 sinx /(x+tanx);

We know already (as in (i) ) that Lt x--> 0 (sinx)/x = 1

Simlarly lt x-->0 (tanx)/x = Lt (sinx)/(xcosx) = 1/cos0 = 1.

Therefore lt x--> 0 (sinx)/(x+tanx) = lt {[(sinx)/x]/[(x+tanx)/x]}. Here we devided both numerator and denominator by x.

Lt x--> 0 (sinx)/(x+tanx) = {lt x-->0 (Sinx)/x}/ {lt x-->0 [(x/x)+(tanx)/x]}

Lt x-->0 (sinx)/(x+tanx) = 1/(1+1) = 1/2

l

We have to find the value of sin (x) / x + tan (x) for lim x-->0.

We can use the Taylor series for sin x

So sin x = x - x^3/3! + x^5/5! ...

=> sin x / x = 1- x^2/ 3! + x^4/ 5! ...

tan x = x + x^3/3 + 2x^5/15 +...

So for lim x--->0

sin x / x = 1- x^2/ 3! + x^4/ 5! ... = 1

and tan x = 0

The expression sin (x) / x + tan (x) for lim x-->0 = 1.

**Therefore the result for sin (x) / x + tan (x) for lim x-->0 = 1.**